The divine Proverb of Streusel : a novel - Brunsvold, Sara, 1979- (Revell, a division of Baker Publishing Group, 2024)
"Shaken by her parents' divorce, Nikki Werner seeks solace at her uncle's farm, leaving her life and relationships behind. She discovers her great-grandmother's notebook full of German recipes and wise sayings. With each recipe she makes, Nikki not only discovers her heritage but also learns to reconnect with what has been scattered"--